Research trends in swimming and diving: A five-year bibliometric analysis (2019-2023) - Arhesa, Sandra; Ma'mun, Amung; Mulyana, Boyke; Sutresna, Nina (Journal Sport Area, 2024)
Background Problems: The field of sports research has experienced varying degrees of development, with certain areas, such as swimming and diving, showing slower progress in publication trends over recent years. Research Objectives: This study aims to provide a comprehensive overview of research trends in swimming and diving over the past five years (2019-2023) using bibliometric analysis. Methods: This study examined 389 Scopus-indexed swimming and diving papers published between 2019 and 2023. Researchers conducted co-word analysis and text mining using VOSviewer to identify key research trends. Finding/Results: The analysis reveals a consistent increase in research trends in swimming and diving, with the United States leading the way in terms of publication output and Indonesia ranking 13th. Influential authors such as Lippmann, John M., Schipke, Jochen D., and Koch, Andreas Edmund, made significant contributions to the field. The majority of publications focus on the sport of swimming, highlighting the research gap in the sport of diving. Conclusion: This bibliometric analysis provides valuable insights in the development of research in the field of swimming and diving, emphasising the need for further research to optimise training methods and improve athlete performance in these sports.